A VIRAL CRISIS: KNOWLEDGE, ATTITUDE AND PRACTICES OF UNDERGRADUATE MEDICAL STUDENTS OF THE TWIN CITIES OF PAKISTAN TOWARDS COVID-19 - Bilal, Arshia; Khan, Aaiz Feroze; Naqvi, Saiyid Ahmad Ali; Shams-ul-Haq, Laiba; Khan, Rukhsana (Journal of Ayub Medical College Abbottabad, 2021)
Background: A novel coronavirus strain, SARS-CoV-2, was identified in December 2019, causing a disease known as coronavirus disease 2019 (COVID-19). WHO declared the COVID-19 emergency as a pandemic in March 2020. Following nationwide lockdowns, it becomes pertinent that the self-quarantined medical students are able to dispense necessary knowledge regarding appropriate prevention practices related to the disease to their respective families and communities, therefore playing a positive role in sharing the economic load of the health system already overburdened by the increasing number of COVID-19 patients. This study aims to investigate the knowledge, attitudes and practices (KAP) of undergraduate medical students of the Twin Cities of Pakistan toward COVID-19, with regards to their observance of precautionary measures against the disease. Methods: Online data in this descriptive cross- sectional study was collected through self-developed questionnaires from 267 undergraduate medical students of twin cities, by convenient sampling. Results: High level of knowledge (72.7%) regarding Covid-19 infection among undergraduate medical students was consistent with their practices (70.8%) but not with their satisfactory attitude (p<0.01). Being female than male and students of private medical colleges showed more satisfactory attitude (p<0.05) and knowledge (p<0.01) towards Covid-19 infection respectively, while practices were more among the students of public sector medical college (p<0.05). Conclusion: The Knowledge of the students was satisfactory and consistent with their practices but not with their Satisfactory attitude, indicating a need to improve upon the prevailing attitude regarding infectious diseases such as Covid-19 and their prevention. Keywords: Covid-19 Pandemic; Medical Students; Knowledge, Attitude and Practices; Pakistan; Prevention